Association between history of cannabis use and outcomes after total hip or knee arthroplasty: a systematic review and meta-analysis - Yang, Guangyao; Li, Feng; Wang, Qiuyuan; Liu, Youwen; Guo, Jiayi; Yue, Chen (Frontiers in Public Health, 2024)
Background Cannabis use may be increasing as countries legalize it and it becomes socially acceptable. A history of cannabis use may increase risk of complications after various kinds of surgery and compromise functional recovery. Here we systematically reviewed and meta-analyzed available evidence on how history of cannabis use affects recovery after hip or knee arthroplasty (THA/TKA). Methods The PubMed, EMBASE, and Web of Science databases were comprehensively searched and studies were selected and analyzed in accordance with the PRISMA guidelines. The methodological quality of included studies was assessed based on the Newcastle-Ottawa Scale, while quality of evidence was evaluated according to the “Grading of recommendations assessment, development, and evaluation” system. Data on various outcomes were pooled when appropriate and meta-analyzed. Results The systematic review included 16 cohort studies involving 5.91 million patients. Meta-analysis linked history of cannabis use to higher risk of the following outcomes: revision (RR 1.68, 95% CI 1.31–2.16), mechanical loosening (RR 1.77, 95% CI 1.52–2.07), periprosthetic fracture (RR 1.85, 95% CI 1.38–2.48), dislocation (RR 2.10, 95% CI 1.18–3.73), cardiovascular events (RR 2.49, 95% CI 1.22–5.08), cerebrovascular events (RR 3.15, 95% CI 2.54–3.91), pneumonia (RR 3.97, 95% CI 3.49–4.51), respiratory failure (RR 4.10, 95% CI 3.38–4.97), urinary tract infection (RR 2.46, 95% CI 1.84–3.28), acute kidney injury (RR 3.25, 95% CI 2.94–3.60), venous thromboembolism (RR 1.48, 95% CI 1.34–1.63), and deep vein thrombosis (RR 1.42, 95% CI 1.19–1.70). In addition, cannabis use was associated with significantly greater risk of postoperative transfusion (RR 2.23, 95% CI 1.83–2.71) as well as higher hospitalization costs. Conclusion History of cannabis use significantly increases the risk of numerous complications and transfusion after THA or TKA, leading to greater healthcare costs. Clinicians should consider these factors when treating cannabis users, and pre-surgical protocols should give special consideration to patients with history of cannbis use.